Factors Affecting the Family Burden of the Palliative Family - Candra Hadi Prasetiya; Emilia Puspitasari Sugiyanto; Wijanarko Heru Pramono (GLOBAL HEALTH SCIENCE GROUP, 2021)
The process of palliative patient care indirectly causes a burden on the family. This study aims to determine the description of the family burden in caring for palliative patients. This study is a qualitative research with a phenomenological study design. Participant criteria are families who care for patients for at least 6 months. The number of respondents in this study were 4 respondents as care givers of palliative patients. The research method using the analysis method used includes categorizing themes, compiling sub-categorization of themes and the last is the coding process. The results of the study showed that there was a description of the family burden of palliative patients and a description of the factors that influenced palliative patients including economic status, patient complaints, family support, family perception, availability of treatment support tools, and the ability of families to manage family burdens. The burden on the family can be reduced by training the family to manage the existing factors.